2018
DOI: 10.1016/j.asjsur.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quercitrin on bacterial translocation in a rat model of experimental colitis

Abstract: In the experimental colitis model established by using DSS, treatment with quercitrin resulted in a histopathological improvement and reduction in biochemical parameters, inflammation and in bacterial translocation (p < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In the present study, C. rodentium -infected mice showed significantly increased levels of proinflammatory cytokines IL-6, TNF-α, and IL-17 in the colonic mucosal tissues compared with the CTRL mice (not infected). It has been demonstrated that quercetin protects against colonic damage linked to increases in the TNF-α level (Donder et al., 2018; Ju et al., 2018). In the present study, quercetin supplementation reduced localized production of inflammatory cytokines, which in turn promoted alterations in bacterial flora composition associated with rapid repair.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, C. rodentium -infected mice showed significantly increased levels of proinflammatory cytokines IL-6, TNF-α, and IL-17 in the colonic mucosal tissues compared with the CTRL mice (not infected). It has been demonstrated that quercetin protects against colonic damage linked to increases in the TNF-α level (Donder et al., 2018; Ju et al., 2018). In the present study, quercetin supplementation reduced localized production of inflammatory cytokines, which in turn promoted alterations in bacterial flora composition associated with rapid repair.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a decrease in BT to liver, spleen, and MLNs was seen after administration of 5 mg/kg/day of quercitrin in the same animal model of intestinal inflammation. This effect was possibly due to the anti-inflammatory properties of the investigated compound, as in the experiment, researchers observed a decrease in TNF-α serum concentration and MPO activity [ 127 ]. Many phytochemicals also exert antioxidant activity, which reduces oxygen-free radical levels and prevents oxidative cellular damage.…”
Section: Dietary Supplements As a Potential Preventative Agents In Btmentioning
confidence: 99%
“…By activating extracellular signal-regulated kinase (ERK) signaling, luteolin may moderate colon tissue damage and reduce inflammation, apoptosis, and autophagy ( Vukelic et al, 2020 ). Luteolin treatment can decrease the activation of NF-κB and production of IL-17 and IL-23, leading to reduced colonic damage in UC rats ( Donder et al, 2018 ). Hyndarin is a compound extracted from corydalis with analgesic and antispasmodic properties, which has the highest concentration in the small intestine 1 hour after administration and effectively relieves spastic pain in UC ( Xiao, 2016 ; Qiu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%